Тенденції удосконалення практичних занять при підготовці здобувачів вищої освіти «Магістр» - Постнікова, Марина Вікторівна; Постникова, Марина Викторовна; Postnikova, Marina; Попова, Ірина Олексіївна; Попова, Ирина Алексеевна; Popova, Iryna (ТДАТУ, 2021)
UK : Запропонована методика проведення практичних занять з дисципліни «Електропривод виробничих машин і механізмів» для здобувачів вищої освіти «Магістр». Для більшої ефективності вивчення дисципліни магістрами доцільно удосконалити практичні заняття методами навчально-наукових досліджень, а саме, наукового методу планування математичного експерименту. EN : The method of conducting practical classes in the discipline «Electric drive of production machines and mechanisms» for applicants for higher education «Master» is proposed. For greater efficiency of studying the discipline by masters, it is advisable to improve practical classes by methods of educational and scientific research, namely, the method of planning a mathematical experiment.
Trends in improving practical classes in the preparation of higher education «Master
Keywords: знання; навчання; самостійна робота; ефективність процесу навчання; навчальна діяльність; планування математичного експерименту; математична модель; структурна схема; knowledge; learning; independent work; efficiency of learning process; educational activity; planning of mathematical experiment